2014
DOI: 10.1007/s12017-014-8333-7
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the Promoter Region of the Survivin Gene is Related to Hemorrhagic Transformation in Patients with Acute Ischemic Stroke

Abstract: Hemorrhagic transformation (HT) of cerebral infarction is a common and serious occurrence following acute ischemic stroke. The expression of survivin, a member of the inhibitor of apoptosis protein family, has been shown to increase after cerebral ischemia. This protein has been mainly located at the microvasculature within the infarcted and peri-infarcted area, so we aimed to investigate whether survivin gene polymorphisms, also known as BIRC5 gene, were associated with HT of cerebral infarction. Polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…One article was designed as a case-control study ( 36 ), and the others were cohort studies. Most studies enrolled patients with all types of acute ischemic stroke, except for three studies including patients without lacunar stroke ( 33 , 34 , 40 ), three studies including patients with cardioembolic stroke involving middle cerebral artery ( 33 35 ), and one study including patients with large-vessel occlusion treated with mechanical thrombectomy ( 54 ). Treatment with thrombolysis varied across studies: 10 studies included patients treated with thrombolysis ( 15 , 27 , 32 , 34 36 , 38 , 42 , 48 , 54 ), four studies had some patients who received thrombolysis ( 19 , 39 41 ), and the remaining 12 studies included patients who did not receive thrombolytic treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One article was designed as a case-control study ( 36 ), and the others were cohort studies. Most studies enrolled patients with all types of acute ischemic stroke, except for three studies including patients without lacunar stroke ( 33 , 34 , 40 ), three studies including patients with cardioembolic stroke involving middle cerebral artery ( 33 35 ), and one study including patients with large-vessel occlusion treated with mechanical thrombectomy ( 54 ). Treatment with thrombolysis varied across studies: 10 studies included patients treated with thrombolysis ( 15 , 27 , 32 , 34 36 , 38 , 42 , 48 , 54 ), four studies had some patients who received thrombolysis ( 19 , 39 41 ), and the remaining 12 studies included patients who did not receive thrombolytic treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 studies comprising 2,631 patients reported on the relationship between MMP-9 levels and hemorrhagic transformation ( 6 , 8 , 15 , 19 , 27 , 32 43 , 45 , 54 ). Of the 19 studies, data from 11 studies with 1,709 patients were meta-analyzed to compare MMP-9 levels between patients with or without hemorrhagic transformation ( 6 , 8 , 15 , 27 , 32 34 , 37 , 38 , 40 , 45 ). The forest plot shows that MMP-9 levels were higher in the hemorrhagic transformation group than in the group without hemorrhagic transformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several polymorphisms have been described in the survivin gene. A recent study has demonstrated that rs17878467 polymorphism of survivin gene is associated with a lower risk of hemorrhagic transformation in patients with ischemic stroke [ 31 ]. The biologic role of amino acid alterations associated with SNPs in ischemic stroke remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke patients presenting this mutation show less severe HT if the HT occur and have lower risk for PH. Survivin is an anti-apoptotic molecule inhibiting caspase-3 [126].…”
Section: Geneticsmentioning
confidence: 99%